Preliminary report on severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) Spike mutation T478K - Di Giacomo, Simone; Mercatelli, Daniele; Rakhimov, Amir; Giorgi, Federico M. (Journal of medical virology, 2021)
Several severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) variants have emerged, posing a renewed threat to coronavirus disease 2019 containment and to vaccine and drug efficacy. In this study, we analyzed more than 1,000,000 SARS‐CoV‐2 genomic sequences deposited up to April 27, 2021, on the GISAID public repository, and identified a novel T478K mutation located on the SARS‐CoV‐2 Spike protein. The mutation is structurally located in the region of interaction with human receptor ACE2 and was detected in 11,435 distinct cases. We show that T478K has appeared and risen in frequency since January 2021, predominantly in Mexico and the United States, but we could also detect it in several European countries. Highlights We analyzed 1,180,571 SARS‐CoV‐2 samples from the public repository GISAID (updated to April 27, 2021). We detected a mutation in SARS‐CoV‐2 Spike (S) protein amino acid 478, S:T478K, which has been growing in sequence in North America (especially Mexico) since January, 2021. S:T478K is one of the characterizing mutations of lineage B.1.1.519, which is currently independent from B.1.1.7 and B.1.351. S:T478K is affecting the Spike binding domain with human receptor ACE2, increasing the electrostatic potential on the interface. Previous experiments show that S:T478K is a possible genetic route for SARS‐CoV‐2 to escape immune recognition.